Safety and efficacy of right portal vein embolization in patients with prior left lateral liver resection. (June 2022) - Van den Bosch, Vincent; Pedersoli, Federico; Keil, Sebastian; Neumann, Ulf P; Kuhl, Christiane K; Bruners, Philipp; Zimmermann, Markus
Background: In patients with bilobar metastatic liver disease, surgical clearance of both liver lobes may be achieved through multiple-stage liver resections. For patients with extensive disease, a major two-staged hepatectomy consisting of resection of liver segments II and III before right-sided portal vein embolization (PVE) and resection of segments V–VIII may be performed, leaving only segments IV ± I as the liver remnant. Purpose: To describe the outcome following right-sided PVE after prior complete resection of liver segments II and III. Material and Methods: In this retrospective study, 15 patients (mean age = 60.4 ± 9.3 years) with liver metastases from colorectal cancer (n = 14) and uveal melanoma (n = 1) who were scheduled to undergo a major two-stage hepatectomy, were included. Total liver volume (TLV) and volume of the future liver remnant (FLR) were measured on pre- and postinterventional computed tomography (CT) scans, and standardized FLR volumes (ratio FLR/TLV) were calculated. Patient data were retrospectively analyzed regarding peri- and postinterventional complications, with special emphasis on liver function tests. Results: The mean standardized post-PVE FLR volume was 26.9% ± 6.4% and no patient developed hepatic insufficiency after the PVE. Based on FLR hypertrophy and liver function tests, all but one patient were considered eligible for the subsequent right-sided hepatectomy. However, due to local tumor progression, only 9/15 patients eventually proceeded to the second stage of surgery. Conclusion: Right-sided PVE was safe and efficacious in this cohort of patients who had previously undergone a complete resection of liver segments II and III as part of a major staged hepatectomy pathway leaving only segments IV(±I) as the FLR.